Prefabricated Urban Underground Utility Tunnels: A Case Study on Mechanical Behaviour with Strain Monitoring and Numerical Simulation - Yonggang Xiao; Jubing Zhang; Jie Cao; Changhong Li (Advances in Materials Science and Engineering)
The prefabricated urban utility tunnels (UUTs) have many advantages such as short construction period, low cost, high quality, and small land occupation. However, there is still a lack of in-depth analysis of the mechanical performance of the prefabricated urban utility tunnel (UUT) structure with bolted connections under different working conditions. In this paper, the force performance of a prefabricated UUT in Tongzhou District, Beijing, was studied under different working conditions using two methods: field monitoring and numerical simulation. The multichannel strain monitor was used for monitoring, and the internal wall concrete and bolt strain change data under the two conditions of installation and backfill were obtained. Combined with the construction process of the UUTs, a three-dimensional numerical model was established by COMSOL, where the build-in bolt assembly was used to simulate the longitudinal connection of the tunnel. The simulation results were compared with the measured data to verify the rationality of the computational model. The simulation results showed that the concrete and bolts on the inner wall of the tunnel work well under the two conditions of installation and backfilling; The deformation of the top plate of the prefabricated tunnel was approximately parabolic, with the largest vertical displacement (0.37 mm) in the middle and the most sensitive to the vertical load in the central part of the roof. The central portion of the side wall had the largest displacement (0.17 mm) in the inner concave. The tensile stress of bolt 3 increased the most (30.75 MPa) but was still much smaller than the yield strength of the bolt. The concrete and bolts of the UUT were found to work well through force analysis under operating conditions. In conclusion, analysis of structural forces and deformation failure modes will help design engineers understand the basic mechanisms and select the appropriate UUT structure.